2018
DOI: 10.1177/0309132518798077
|View full text |Cite
|
Sign up to set email alerts
|

Global environmental change I: Climate resilient peace?

Abstract: This report uses a critique of the ontology of research on climate change and armed conflict to advance a positive and performative account of the ways in which peace could be sustained and expanded through a changing climate. Focussing on research into the relationships between climate change and armed conflict and peace, it argues that recent debates about the effect of climate change on conflagrations stem from deeper assumptions about the way the world is and can be known. The report then builds an alterna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(26 citation statements)
references
References 83 publications
2
24
0
Order By: Relevance
“…By focusing on the six components of the DRM Assemblage, research using the framework is directed to understanding, critiquing and potentially challenging the ways in which diverse techniques and technologies of DRM attempt to manage uneven relationships of a more-than-human life (Anderson, 2012;Donovan, 2017). A focus on 'root causes' is replaced by a focus on how place-specific political, scientific, economic and social imaginations become dominant futures-in-themaking and how these imagined futures interact with uncertain more-than-human hazards to lead to the continued territorialisation of inequalities and vulnerabilities in disaster events (Barnett, 2018(Barnett, , 2020Granjou et al, 2017;Grove, 2014b). The way in which these vulnerabilities might be understood and addressed is explored not only through transdisciplinary hazard assessments and radical disaster studies (Gaillard, 2019) but also through the literature on feminist ethics of care and sustainability (de La Bellacasa, 2017;Kinkaid, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…By focusing on the six components of the DRM Assemblage, research using the framework is directed to understanding, critiquing and potentially challenging the ways in which diverse techniques and technologies of DRM attempt to manage uneven relationships of a more-than-human life (Anderson, 2012;Donovan, 2017). A focus on 'root causes' is replaced by a focus on how place-specific political, scientific, economic and social imaginations become dominant futures-in-themaking and how these imagined futures interact with uncertain more-than-human hazards to lead to the continued territorialisation of inequalities and vulnerabilities in disaster events (Barnett, 2018(Barnett, , 2020Granjou et al, 2017;Grove, 2014b). The way in which these vulnerabilities might be understood and addressed is explored not only through transdisciplinary hazard assessments and radical disaster studies (Gaillard, 2019) but also through the literature on feminist ethics of care and sustainability (de La Bellacasa, 2017;Kinkaid, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the sample includes reviews published in every year since 2012 to 1 As of 1 October 2020, the 2012 JPR special issue articles had been cited a total of 1,574 times in the Web of Science database. 2 The reviews included in this assessment are : Deligiannis, 2012;Scheffran et al, 2012a,b;Hsiang, Burke & Miguel, 2013;Klomp & Bulte, 2013;Meierding, 2013;Theisen, Gleditsch & Buhaug, 2013;Gemenne et al, 2014;Hsiang & Burke, 2014;Salehyan, 2014;Selby, 2014;Selby & Hoffmann, 2014;Zografos, Goulden & Kallis, 2014;Buhaug, 2015Buhaug, , 2016Burke, Hsiang & Miguel, 2015;Gartzke & Böhmelt, 2015;Burrows & Kinney, 2016;Seter, 2016;Abrahams & Carr, 2017;Gilmore, 2017;Ide, 2017;Koubi, 2017Koubi, , 2019Sakaguchi, Varughese & Auld, 2017;Theisen, 2017;Adams et al, 2018;Busby, 2018;van Baalen & Mobjörk, 2018;Barnett, 2019;Mach et al, 2019Mach et al, , 2020Pearson & Newman, 2019;Bernauer & Böhmelt, 2020;Vesco et al, 2020. These reviews were identified by consulting hits to a Google Scholar search for the terms 'climate ', 'conflict', and 'review', published since 2011. allow tracing systematic changes in assessments over time, and the sample comprises author teams spanning disciplines, institutions, and review methods to minimize bias.…”
Section: Seven Historical Priorities For Climate-conflict Research Anmentioning
confidence: 99%
“…Steps to address climate vulnerabilities are suggested to advance peace by contributing to community resilience (e.g., Matthew 2018). Ideas about climate resilient peace stem from key insights: factors addressing vulnerability and facilitating climate adaptation help mitigate armed conflict during environmental change; environmental cooperation can ease tensions and build trust between (conflicting) parties; and focusing on resilience rather than security discourses and practices promotes peaceful adaptation (Barnett 2019). Considering both vulnerability and resilience to be politically produced and situated, I take this as a starting point from which to conceptualize climate resilient peace with a focus on power structures.…”
Section: Conceptualizing Climate Resilient Peacementioning
confidence: 99%